'11 November 1918, an exceptional day!': Flashbulb memories of the World War I Armistice in Belgium from a psychological and a historical perspective. (July 2017) - Luminet, Olivier; Spijkerman, Rose
Flashbulb memories are memories that are consistent, vivid, detailed and retained with high confidence for the circumstances in which people heard about distinctive and emotional news. We show that under some circumstances, flashbulb memories can distort the memory people will keep for (historical) events, and in other situations, flashbulb memories can strengthen them. Subsequently, we present historical sources indicating that remote flashbulb memories can be studied under methodologically sound conditions. Using the Armistice of the World War I in Belgium as a case study, we hope to make historians more aware of the existence and importance of flashbulb memories in historical sources. This may provide new perspectives for understanding the significance of events and the ways through which historical narratives are reconstructed.